Preparation of Cobalt-Silica Dioxide (CoxSiO2) Catalyst through Impregnation Method - Isthifaul Mawaddah; M. Pranjoto Utomo (Indonesian Journal of Chemistry and Environment, 2022)
The CoxSiO2 catalyst have been synthesized by reacting amount of cobalt nitrate and silica dioxide through impregnation method with vatiation on x= 0, 0.025, 0.05, and 0.1. The resulted materials were characterized using UV-Vis DRS, FT-IR, XRD, and SEM-EDX instruments. The XRD results showed that Co-SiO2 catalyst have peaks at 2θ of 21.5º (for x = 0.025), 14.52º (for x = 0.05), and 21.58º (for x = 0.1). The CoxSiO2 catalysts were amorphous with average size of 4-11 nm and the band gap were at around of 1-3 eV.